Metachronous carcinomas colon and pancreas - Praderi, Raúl; Boudrandi, Sonia; Rodríguez, Gustavo; Navarrete, Héctor (Cirugía del Uruguay, 1996)
Two patients, one male and one fema/e, were operated upan successively of right colon cancer and of pancreas head, the former, and of cephalic pancreas carcinoma and of the rectum, the latter. The tour tumors were resected onco/ogical/y. Fol/owing the pancreatic resections they were reconstructed by different techniques. The fema/e patient has undergone two years and the male one year of pancreatic resection as we/1 as the same reverse figures related to the co/ic resections. Stress is laid on the rare coincidence of these tumors as reported by the literature.